Positive electrode active material and battery using it

JP2026167239APending Publication Date: 2026-10-14SUMITOMO METAL MINING CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
JP2025060714
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2025-04-01
Publication Date
2026-10-14

AI Technical Summary

Benefits of technology

【0012】 本発明によれば、活物質粒子を、イオン伝導性と電子伝導性の両方を有する被覆層で被覆してから電解液に浸漬することで、活物質へのイオン伝導と電子伝導の経路を維持しつつ活物質と電解液の反応や活物質からの成分の溶出を防ぐことができる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2026167239000001_ABST
    Figure 2026167239000001_ABST
Patent Text Reader

Abstract

This invention provides a battery with superior battery characteristics, as it can suppress the degradation of the electrolyte even when immersed in the electrolyte. [Solution] The present invention relates to a positive electrode active material having a core of positive electrode active material particles and a coating layer provided on the surface of the core, characterized in that the coating layer consists of a mixture of a conductive material and a solid electrolyte.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a battery structure, and more particularly to a battery in which the relationship between an electrolyte and an active material, particularly a positive electrode active material, is considered.

Background Art

[0002] Conventionally, battery technology that causes a battery reaction to occur by immersing an active material in an electrolytic solution or bringing the active material into contact with a solid electrolyte is widely and generally known. Here, as problems of such conventional technologies, there is a problem that battery characteristics are degraded due to the reaction of the active material with the electrolytic solution or the elution of components of the active material into the electrolytic solution (for example, see Patent Document 1), and in the case of a battery using a solid electrolyte, there is a problem that it is necessary to apply a restraining pressure to maintain the contact between the active material and the solid electrolyte, which may complicate the structure (for example, see Patent Document 2).

Prior Art Documents

Patent Documents

[0003]

Patent Document 1

Patent Document 2

Summary of the Invention

Problems to be Solved by the Invention

[0004] The present invention has been made in view of such conventional problems, and provides a battery with excellent battery characteristics that uses an active material, particularly a positive electrode active material, which has a structure capable of suppressing deterioration of the electrolytic solution and the active material even in a state of being immersed in the electrolytic solution and does not need to apply a restraining pressure while using a solid electrolyte.

Means for Solving the Problems

[0005] In other words, according to one aspect of the present invention for solving the above problems, the first aspect of the present invention is a positive electrode active material having a core of positive electrode active material particles and a coating layer provided on the surface of the core, wherein the coating layer is made of a mixture of a conductive material and a solid electrolyte.

[0006] A second aspect of the present invention is a positive electrode active material having a core of positive electrode active material particles and a coating layer provided on the surface of the core, wherein the coating layer is composed of an electronically conductive solid electrolyte, the electronic conductivity of the coating layer is greater than the electronic conductivity of the positive electrode active material, and the density of the coating layer ρ c However, the positive electrode active material is characterized by having a true density ρ0 of the solid electrolyte of 50% to 90% and a coating layer thickness of 5 nm to 100 nm.

[0007] A third aspect of the present invention is a positive electrode active material characterized in that the particles of the positive electrode active material in the first or second aspect are a lithium oxide containing manganese.

[0008] A fourth aspect of the present invention is a positive electrode active material characterized in that, in the third aspect, nickel accounts for 70% or more of the transition elements contained therein, in terms of atomic number.

[0009] A fifth aspect of the present invention is a positive electrode active material characterized in that, in the third aspect, the proportion of manganese among the transition elements contained is 20% or more in terms of atomic number.

[0010] A sixth aspect of the present invention is a positive electrode active material characterized in that the positive electrode active material in the first or second aspect is sulfur or a sulfur compound.

[0011] A seventh aspect of the present invention is a battery comprising a battery electrode containing the positive electrode active material described in the first or second aspect, wherein the battery electrode is immersed in an electrolyte. Furthermore, an eighth aspect of the present invention is a battery comprising a battery electrode containing the positive electrode active material described in the third aspect, characterized in that the battery electrode is immersed in an electrolyte. [Effects of the Invention]

[0012] According to the present invention, by coating active material particles with a coating layer having both ionic and electronic conductivity and then immersing them in an electrolyte, it is possible to maintain the pathways for ionic and electronic conduction to the active material while preventing reactions between the active material and the electrolyte, as well as the elution of components from the active material. [Brief explanation of the drawing]

[0013] [Figure 1] This is a cross-sectional diagram of a positive electrode active material according to a first aspect of the present invention. [Figure 2] This is a cross-sectional diagram of a positive electrode active material according to a second aspect of the present invention. [Figure 3] This is a cross-sectional diagram of a positive electrode active material according to conventional technology. [Modes for carrying out the invention]

[0014] Figures 1 and 2 show cross-sectional diagrams of the positive electrode active material according to the present invention, and Figure 3 shows a cross-sectional diagram of a positive electrode active material according to the prior art. Figure 1 is a cross-sectional diagram of the positive electrode active material according to the first embodiment of the present invention, and Figure 2 is a cross-sectional diagram of the second embodiment.

[0015] In Figure 1, 1A represents a positive electrode active material according to a first embodiment of the present invention, 10 is a core particle of the positive electrode active material, 11 is a coating layer (a mixture of an ion-conductive solid electrolyte 12 and a conductive material 13), 12 is an ion-conductive solid electrolyte, and 13 is a conductive material. In Figure 2, 1B is a positive electrode active material according to a second aspect of the present invention, 10 are particles of the core positive electrode active material, and 12a is a solid electrolyte that possesses both electronic and ionic conductivity, and at the same time, is a solid electrolyte that constitutes the coating layer. These positive electrode active materials are mixed with conductive additives such as carbon powder as needed, and then kneaded with a binder to form an electrode mixture. By immersing the electrode mixture alone, or with the electrode mixture placed on a current collector, in an electrolyte solution, a battery electrode with predetermined battery characteristics is obtained.

[0016] Regarding the thickness of the aforementioned coating layer 11 and the thickness of the solid electrolyte 12a having electron conductivity that also serves as a coating layer, for the coating layer 11 made of a mixture containing the conductive substance 13, a thickness equal to or greater than the average particle diameter of the contained conductive substance 13, or a thickness less than the maximum particle diameter, is required such that the surface of the conductive substance 13 is exposed from the layer formed by the solid electrolyte 12 constituting the matrix of the coating layer 11. (See Figure 1.)

[0017] Further, the thickness of the solid electrolyte 12a having electron conductivity as a coating layer is selected in consideration of the ionic conductivity of the solid electrolyte used and the thickness of the coating layer, such that the ionic conduction resistance of the coating layer does not become larger than the ionic conduction resistance of the surface of the positive electrode active material without the coating layer. (See Figure 2.) Such a thickness of the coating layer is desirably 5 nm to 100 nm. If the thickness of the coating layer is less than 5 nm, the effect of suppressing the reaction between the positive electrode active material and the electrolytic solution and the elution of components from the positive electrode active material is reduced, which is not preferable. If the thickness of the coating layer exceeds 100 nm, the ionic conduction resistance of the coating layer becomes larger than the ionic conduction resistance of the layer 21 generated by the reaction between the surface of the particles of the positive electrode active material 2 according to the related art and the electrolytic solution, which is not preferable. (See Figure 3.) Further, the density ρ of the coating layer formed by the solid electrolyte 12a c is desirably 50 to 90% of the true density ρ0 of the substance constituting the solid electrolyte 12a. The density ρ of the coating layer c If it is less than 50% of the true density ρ0 of the substance constituting the solid electrolyte 12a, the mechanical strength of the coating layer will be low, and the possibility of the coating layer being destroyed in the step of producing the electrode mixture from the positive electrode active material increases, which is not preferable. If the true density ρ0 of the substance constituting the solid electrolyte 12a exceeds 90%, it becomes difficult for the primary particles constituting the positive electrode active material covered with the coating layer to come into contact with the electrolytic solution, which is not preferable.

[0018] The present invention has an aspect of a positive electrode active material (Fig. 1, reference numeral 1A) having a structure in which particles 10 of the positive electrode active material serve as a core, and a coating layer 11 of a mixture of a solid electrolyte and a conductive material is provided on the outer peripheral surface (i.e., the surface) thereof, or a positive electrode active material (Fig. 2, reference numeral 1B) having a structure provided with a coating layer 12a made of a solid electrolyte having both ionic conductivity and electronic conductivity. As described above, since the positive electrode active material according to the present invention adopts the structure having the above characteristics, by being immersed in an electrolytic solution to cause a battery reaction to occur, while maintaining the paths for ionic conduction and electronic conduction to the positive electrode active material, it functions to prevent elution of components from the positive electrode active material and suppress deterioration of battery characteristics.

[0019] It should be noted that the positive electrode active material according to the present invention can be used in either primary batteries or secondary batteries, and exhibits the effect of suppressing deterioration of battery characteristics. In particular, as the positive electrode active material particles serving as the core, lithium oxides containing manganese such as NMC (LiNiMnCoO₂) and LMO (LiMn₂O₄) are suitable, and sulfides such as S₈ and Li₂S may also be used. Among NMC materials, those containing nickel in an atomic number of 70% or more of the total atomic number of nickel, manganese, and cobalt are particularly suitable due to their high reactivity with the electrolytic solution, and those containing manganese in an atomic number of 20% or more of the total atomic number of nickel, manganese, and cobalt are particularly suitable because manganese is likely to be eluted. Further, as the solid electrolyte to be used, a sulfur-based solid electrolyte such as Li₂S-P₂S₅, or Li₇La₃Zr₂O 12 An oxide-based solid electrolyte such as (LLZ) is suitable. Furthermore, for the solid electrolyte having electronic conductivity in combination, it is preferable to use a metal oxide such as a LaCoO₃-based material, a LaMnO₃-based material, or a LaFeO₃-based material. As the electrolytic solution used when forming a battery, it is desirable to use a carbonate-based electrolytic solution such as LiPF₆ EC / DEC or LiPF₆ EC / EMC, or an ether-based electrolytic solution such as 1M LiTFSA DOL / DME. [Examples]

[0020] The following describes in detail an embodiment of the present invention, specifically a "positive electrode active material," with reference to examples. However, the present invention is not limited to these examples. [Examples]

[0021] A mixture was obtained by adding nitrate of La, nitrate of Co, and polyethylene glycol (PEG) to water and mixing. LiNiMnCoO2 (NMC) powder with an average particle size of 5 μm was placed in a rolling fluidized bed granulator, and the mixture was sprayed onto it. The NMC powder was dried in a fluidized state, and an NMC powder with a coating layer precursor on its surface was obtained. When the NMC powder was calcined at 600°C for 3 hours, the nitrate of La and the nitrate of Co transformed into a film of LaCoO3 with a thickness of approximately 50 nm, and the polyethylene glycol transformed into carbon particles with an average particle size of 100 nm, resulting in a positive electrode active material made of NMC covered with a coating layer. The LaCoO3 film is a solid electrolyte with lithium ion conductivity, and the carbon particles are conductive particles. [Examples]

[0022] A positive electrode active material consisting of NMC covered with a coating layer was obtained using the same process as in Example 1, except that PEG was not added in the preparation of the mixture. Since PEG was not added, the coating layer did not contain carbon particles.

[0023] (Conventional example 1) The NMC powder used in Examples 1 and 2 was used directly as the positive electrode active material.

[0024] (evaluation) Positive electrodes were obtained by mixing, kneading, and molding the active materials of Example 1, Example 2, and Conventional Example 1 with a conductive additive (carbon black) and a binder. A lithium metal was used for the negative electrode, and a battery evaluation was performed using 1M LiPF6EC / DEC (volume ratio 1:1) as the electrolyte. After measuring the internal resistance of the battery, the battery was placed in a constant temperature bath at 40°C and charged at a constant voltage of 4V for 24 hours. The internal resistance of the battery was then measured again, and the amount of Mn deposited on the negative electrode was measured after disassembly.

[0025] The internal resistance of the batteries before the charging test was (conventional example 1 battery) < (example 1 battery) < (example 2 battery), and the internal resistance of the batteries after the charging test was (example 1 battery) < (example 2 battery) < (conventional example 1 battery). Furthermore, the amount of Mn deposited on the negative electrode was approximately (battery of Example 1) ≈ (battery of Example 2) < (conventional example 1).

[0026] The following can be seen from the test results. In the conventional battery example 1, the initial internal resistance was low because the active material lacked a coating layer. However, after charging, the internal resistance increased due to the leaching of Mn from the NMC of the active material. In the battery of Example 2, the increase in resistance due to charging was suppressed because the elution of Mn was suppressed by the coating layer of the active material. However, the initial internal resistance was high because the electron conductivity of LaCoO3, which is the coating layer of the active material, was insufficient. In contrast to these, in the battery of Example 1, the presence of highly conductive carbon particles in the coating layer suppressed the initial internal resistance, and the coating layer prevented the leaching of Mn from the active material, thereby suppressing the increase in resistance due to charging. [Examples]

[0027] Sulfur powder with an average particle size of 5 μm, LaCoO2 powder with an average particle size of 50 nm, and graphite powder with an average particle size of 100 nm were mixed, water was added to form a slurry, and the mixture was then mixed in a bead mill. This slurry was then spray-dried at 80°C. The surface of the resulting sulfur powder was coated with LaCoO2 powder and graphite powder. [Examples]

[0028] Except for not adding graphite powder during slurry preparation, the sulfur powder coated with LaCoO2 powder was obtained using the same procedure as in Example 3.

[0029] (Conventional example 2) The sulfur powder used in Examples 3 and 4 was used directly as the positive electrode active material.

[0030] (evaluation) Except for using the active materials from Example 3, Example 4, and Conventional Example 2, and using 1M LiTFSA DOL / DME (volume ratio 1:1) as the electrolyte to fabricate batteries, and disassembling the batteries after measurement to measure the amount of sulfur deposited on the negative electrode, the evaluation was carried out in the same manner as the evaluation of batteries using the active materials from Example 1, Example 2, and Conventional Example 1. Here, "LiTFSA" is lithium bis(trifluoromethanesulfonyl)amide, "DOL" is 1,3-dioxolane, and "DME" is dimethoxyethane.

[0031] The following can be seen from the test results. The internal resistance of the batteries before the charging test was (conventional example 2 battery) < (example 3 battery) < (example 4 battery), and the internal resistance of the batteries after the charging test was (example 3 battery) < (example 4 battery) < (conventional example 2 battery).

[0032] Furthermore, the amount of sulfur deposited on the negative electrode was approximately (battery of Example 3) ≈ (battery of Example 4) < (conventional example 2).

[0033] In the conventional battery example 2, the initial internal resistance was low because the active material lacked a coating layer, but after charging, the internal resistance increased due to the leaching of sulfur from the active material. In the battery of Example 4, the increase in resistance due to charging was suppressed because the sulfur leaching was suppressed by the coating layer of the active material. However, the initial internal resistance was high because the electron conductivity of LaCoO3, which is the coating layer of the active material, was insufficient. In contrast to these, in the battery of Example 3, the presence of highly conductive carbon particles in the coating layer suppressed the initial internal resistance, and the coating layer prevented sulfur leaching from the active material, thus suppressing the increase in resistance due to charging. [Explanation of Symbols]

[0034] 1A, 1B Positive electrode active material according to the present invention 10. Particles of the positive electrode active material 11 Covering layer 12. Solid electrolytes (possessing ionic conductivity) 12a Solid electrolytes possessing both ionic and electronic conductivity 13 Conductive materials 2. Cathode active material related to the prior art 21 Layer formed by the reaction between the positive electrode active material and the electrolyte.

Claims

1. A positive electrode active material having a core composed of positive electrode active material particles, with a coating layer provided on the surface of the core, The positive electrode active material is characterized in that the coating layer consists of a mixture of a conductive substance and a solid electrolyte.

2. A positive electrode active material having a core composed of positive electrode active material particles, with a coating layer provided on the surface of the core, The coating layer is composed of an electronically conductive solid electrolyte, The electronic conductivity of the coating layer is greater than the electronic conductivity of the positive electrode active material. The density ρ of the coating layer c However, the true density ρ of the solid electrolyte 0 50% to 90% A positive electrode active material characterized in that the thickness of the coating layer is 5 nm to 100 nm.

3. The positive electrode active material according to claim 1 or 2, characterized in that the particles of the positive electrode active material are a lithium oxide containing manganese.

4. The positive electrode active material according to claim 3, characterized in that nickel accounts for 70% or more of the transition elements contained therein, in terms of atomic number.

5. The positive electrode active material according to claim 3, characterized in that the proportion of manganese among the transition elements contained is 20% or more in terms of atomic number.

6. The positive electrode active material according to claim 1 or 2, characterized in that the positive electrode active material is sulfur or a sulfur compound.

7. A battery comprising a battery electrode containing the positive electrode active material described in claim 1 or 2, wherein the battery electrode is immersed in an electrolyte.

8. A battery comprising a battery electrode containing the positive electrode active material described in claim 3, wherein the battery electrode is immersed in an electrolyte.

Citation Information

Patent Citations

  • Nonaqueous electrolyte secondary battery

    JP2000077071A

  • All-solid battery

    JP2012048853A